Customer satisfaction in ISO 9001 certified and non-ISO 9001 certified Higher Education Institution (HEI) libraries in Central Luzon - Tongol, Reyma R.; Apolinario, Rhea Rowena U.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2015)
The study aimed to find the significant difference in the level of customer satisfaction between ISO 9001 and non-ISO 9001 certified HEI libraries in Central Luzon using the Libqual+TM service quality dimensions: Effect of Service, Information Control and Library as a Place. It also aimed to find out the current level of customer satisfaction with the ISO 9001 and the non-ISO 9001 certified HEI libraries in Central Luzon.
A descriptive research design was used in the study. The respondents were the internal and external customers of the nine (9) HEI libraries in Central Luzon. The 193 respondents came from the ISO 9001 certified HEIS while 250 respondents came from the non-ISO 9001 certified HEI libraries in Central Luzon.
The data were collected using survey questionnaires. Frequency count, means and percentage were computed. The independent sample t-test was used to determine the difference in the Libqual+TM mean scores of the two groups of libraries.
Based on the findings of the study, ISO 9001 and non-ISO 9001 certified HEI libraries in Central Luzon do not differ significantly in their level of customer satisfaction, except for the two aspects of Libqual+TMEffect of Service dimension: AS1-ability of library staff to develop confidence in customers (p=.006), and; AS9 - ability of the library staff to manage customer service problems (p=.029).
Overall, ISO 9001 certified and the Non-ISO 9001 certified libraries in Central Luzon do not differ significantly on their general customer satisfaction. Due to the slight differences found, it can be concluded that ISO 9001 standard has little impact on the level of library customer satisfaction. It can further be concluded that ISO 9001 standard may serve as an option that libraries can use in assessing customer satisfaction.
Special Problem (Master of Library and Information Science)
Keywords: Consumer satisfaction -- Philippines -- Central Luzon; ISO 9001 Standard; Academic libraries -- Philippines -- Central Luzon